Influence of Carbon and Microbial Community Priming on the Attenuation of Uranium in a Contaminated Floodplain Aquifer. Issue 4 (21st July 2014) - Mouser, P.J.; N'Guessan, L.A.; Qafoku, N.P.; Sinha, M.; Williams, K.H.; Dangelmayr, M.; Resch, C.T.; Peacock, A.; Wang, Z.; Figueroa, L.; Long, P.E.
Abstract The capacity for subsurface sediments to sequester radionuclide contaminants, such as uranium (U), and retain them after bioremediation efforts are completed is critical to the long‐term stewardship of re‐mediated sites. In U bioremediation strategies, carbon amendment stimulates bioreduction of U(VI) to U(IV), immobilizing it within the sediments. Sediments enriched in natural organic matter are naturally capable of sequestering significant U, but may serve as sources to the aquifer, contributing to plume persistence. Two types of organic‐rich sediments were compared to better understand U release mechanisms. Sediments that were artificially primed for U removal were retrieved from an area previously biostimulated while detrital‐rich sediments were collected from a location never subject to amendment. Batch incubations demonstrated that primed sediments rapidly removed uranium from the groundwater, whereas naturally reduced sediments released a sizeable portion of U before U(VI)‐reduction commenced. Column experiments confirmed that U release persisted for 65 pore volumes in naturally reduced sediments, demonstrating their sink‐source behavior. Acetate addition to primed sediments shifted the microbial community from sulfate‐reducing bacteria within Desulfobacteraceae to the iron‐reducing Geobacteraceae and Firmicutes, associated with efficient U(VI) removal and retention, respectively. In contrast, Geobacteraceae communities in naturally reduced sediments were replaced by sequences with similarity to Pseudomonas spp. during U release, while U(VI) removal only occurred with enrichment of Firmicutes. These investigations stress the importance of characterizing zones with heterogeneous carbon pools at U‐contaminated sites prior to the determination of a remedial strategy to identify areas, which may contribute to long‐term sourcing of the contaminants.